The Implementation Of Rehabilitation For Narcotics Abusers And The Proportionality Of Sentencing In Indonesian Narcotics Law - Ahmad Helmi Attamimi; Wahyu Prawesthi; Ernu Widodo (Jurnal Ragam Pengabdian, 2026)
Narcotics abuse presents a complex challenge for law enforcement in Indonesia, requiring a balance between combating illicit drug circulation and protecting individuals who misuse narcotics through rehabilitative measures. Law No. 35 of 2009 mandates rehabilitation for narcotics abusers and addicts, particularly under Article 54 and Article 127 paragraph (3). However, in practice, sentencing policies still predominantly favor imprisonment, resulting in disproportionate punishment and contributing significantly to prison overcrowding. This study examines: (1) the implementation of rehabilitation for narcotics abusers under Article 127 paragraph (3) of Law No. 35 of 2009 in law enforcement practice, and (2) the proportionality of sentencing when assessed against the objectives of punishment and the principle of substantive justice. Using normative legal research methods, this study applies statutory, conceptual, and case-study approaches, supported by primary legal materials, judicial guidelines, and relevant academic literature. The findings indicate that the application of rehabilitation remains inconsistent due to heavy reliance on assessment mechanisms and broad judicial discretion, leading to sentencing disparities ranging from rehabilitation orders to imprisonment or combined sanctions. As a result, punishment imposed on narcotics abusers often fails to meet the standard of proportionality. The study argues that rehabilitation should constitute the primary response for pure narcotics abusers in order to align sentencing practices with restorative objectives and substantive justice.